A study on the post-IPO operating performance using the pre-IPO chracteristics and performance of publicly listed companies in Singapore from 2010-2016 - Catalig, Peter John E. (Animo Repository, 2017)
This paper is about the operating performance of select publicly listed Singaporean firms. Specifically, it discusses whether the operating performance before the initial public offering (IPO) is significantly different after their issuance. Using the return on assets (ROA), the return on sales (ROS), and the total asset turnover (ATO) as the basis of a company's operating performance, this research also investigates if certain pre-IPO characteristics such as age, firm, size, dilution of ownership, pre-IPO profitability, and the board size have any significant relationship with the post-IPO performance of companies. Out of the sixteen (16) Singaporean firms that issued an IPO in 2013, it was found that pre-operating performances in 2012 are significantly different from immediate post-IPO years. Thsi study has observed that the post-IPO profitability of a firm has a significant relationship with several pre-IPO characteristics, namely board size, dilution of ownership and pre-IPO profitability.